Wave slam on wave piercing catamarans in random head seas. (1st May 2017) - Davis, M.R.; French, B.J.; Thomas, G.A.
Abstract: A hydro-elastic 2.5 m wave piercing catamaran model with a short centre bow has been tested in random head seas. Slamming wave impacts were found to be close to the aft end of the short centre bow. These occurred at time intervals of over 3 encountered modal wave periods, with longer intervals in smaller seas and for shorter modal periods. Slams were only detected in wave heights exceeding 1.5 m at full scale. Slam loads in 4 m seas were mostly about 25% of the hull weight but some reached 132% of the hull weight. Slam durations were generally about 0.35 s at full scale. Slam induced bending was found to reach 11% of the product of hull weight and length. Simulation of slamming within a time domain seakeeping computation showed slightly higher median relative velocities at the slam instant than was observed in the model tests. Highlights: Model testing for wave slam of a high speed catamaran ferry in random seas. The test data forms the basis of an empirical model of wave slamming. The empirical model is incorporated in a high speed ship motion computation program. The program is applied to the prediction of slam occurrence rates and slam loading.